Analisis Faktor Penyebab Perceraian di Pengadilan Agama Nganjuk Tahun 2017–2019 Perspektif Kompilasi Hukum Islam - Abd. Basit Misbachul Fitri; Halimatus Sa’adah (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2026)
This study aims to analyze divorce cases at the Nganjuk Religious Court during 2017–2019 from the perspective of the Indonesian Compilation of Islamic Law (Kompilasi Hukum Islam/KHI). Specifically, the research examines the number of divorce cases, identifies the dominant factors causing divorce, and analyzes their conformity with the legal provisions governing divorce under the KHI. This study employs a qualitative empirical legal research method with a field research approach. Primary data were obtained through interviews with judges and court officials of the Nganjuk Religious Court, while secondary data were collected from court documents, legislation, and relevant literature. Data were gathered through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, with source triangulation employed to ensure data validity. The findings indicate that divorce cases remained consistently high during the 2017–2019 period, with divorce petitions filed by wives (cerai gugat) significantly exceeding divorce petitions filed by husbands (cerai talak). Economic problems constituted the most dominant cause of divorce, followed by continuous marital disputes and abandonment by one spouse. From the perspective of the Compilation of Islamic Law, the causes of divorce identified in this study generally correspond to the grounds for divorce stipulated in Article 116 of the KHI. In judicial practice, however, judges more frequently rely on Article 19 letter (f) of Government Regulation Number 9 of 1975 concerning continuous disputes and the impossibility of reconciliation as the principal legal basis for granting divorce.